Pengaruh Pengetahuan, Motivasi serta Independensi terhadap Kualitas Audit Internal di Bank Perkreditan Rakyat (BPR) Kota Malang - Nifanngeljau, Johanis; Mukoffi, Ahmad (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p20, 2021)
The purpose of this research was made to be able to analyze and provide facts related to the existence of knowledge, motivation, and independence can have an influence on the quality of audits in this research in the form of survey analysis method which will use questionnaires in a way to be able to collect a variety of data needed. The purpose of distributing this questionnaire to employees in this case auditors in 5 BPR Malang city with the number of auditors 30 respondents. The level of quality of data that can be generated from the user of the research instrument and evaluated by testing the validity of the data. Hypothetical testing will use multiple linear regress data analysis techniques. Based on the results of the research, it can be known that three independent variables can have a significant and positive and negative influence on the quality of audits . Keywords: Knowledge; Motivation; Independence on Audit Quality.